Dog Blue - Dunbar, Polly (Cambridge, Mass. : Candlewick Press, 2004)
Bertie, who loves the color blue and really wants a dog, finally gets his wish even though the dog he meets is white with black spots.
Accelerated Reader AR
Keywords: Dogs -- Fiction; Blue -- Fiction; Imagination -- Fiction